Activating Students to Speak English by Using ELTIS Resource Pack - Nur Fadillah Nurchalis; Selviana Selviana; Effran Ade Riza (Loquen, 2019)
Students are mostly talkative outside the classroom, but in English class, they are more apathetic. This research aims to examine how English Language Training for Islamic Schools (ELTIS) resource pack is able to activate students’ to speak English. This research is designed as Classroom Action Research (CAR) which is specific to collaborative action research. The subjects of this research are 25 students of the eighth class of MTs Pacongan Pinrang in the academic year 2019/2020. Instruments of the research test, observation checklist, and interview. The test aims to gain quantitative data, while the observation checklist and interview aim to gain qualitative data. The result finds that the use of various media available in ELTIS Resource Pack activates students to speak English. A variety of learning media reduces students’ boredom and engages students during the learning process enthusiastically.